Proposal to obtain the maximum floor accelerations using the Peruvian seismic standard e.030 - Sánchez Meza, Roque Alberto (2022)
In this work, a simplified envelope is proposed for the calculation of floor accelerations necessary for the design of diaphragms or slabs in reinforced concrete buildings. This envelope has been calibrated using the results of non-linear time-history analysis of analytical building models and measurements obtained from specimens tested on a shaking table at different universities. The proposed acceleration envelope is constructed only using their respective values ​​at the base, at the last level and the participation of the shear walls in the structural system, which makes its implementation simple for use in engineering practice.